Acanthus montanus: An experimental evaluation of the antimicrobial, anti-inflammatory and immunological properties of a traditional remedy for furuncles - Nwoye Anthonia C; Okoye Theophine C; Onuoha Nkemjika J; Akah Peter A; Okoli Charles O; Nworu Chukwuemeka S (BMC, 2008)
Abstract Background Acanthus montanus (Nees) T. Anderson (Acanthaceae) is a shrub widespread in Africa, the Balkans, Romania, Greece and Eastern Mediterranean. It is used in African traditional medicine for the treatment of urogenital infections, urethral pain, endometritis, urinary disease, cystitis, leucorrhoea, aches and pains. In southeastern Nigeria, the root is popular and acclaimed highly effective in the treatment of furuncles. This study was undertaken to experimentally evaluate the antimicrobial and anti-inflammatory properties of the root extract as well as its effect on phagocytosis and specific cell-mediated immune response which may underlie the usefulness of the roots in treatment of furuncles. Methods The aqueous root extract (obtained by hot water maceration of the root powder) was studied for effects on the growth of clinically isolated strains of Pseudomonas aeruginosa and Staphylococcus aureus. The anti-inflammatory activity was investigated using acute topical edema of the mouse ear induced by xylene, acute paw edema induced by agar in rats, formaldehyde arthritis in rats, vascular permeability induced by acetic acid in mice and heat- and hypotonicity-induced haemolysis of ox red blood cells (RBCs). Also evaluated were the effects on in vivo leukocyte migration induced by agar, phagocytic activity of macrophages on Candida albicans and specific cell-mediated immune responses (delayed type hypersensitivity reaction (DTHR) induced by sheep red blood cell (SRBC)). The acute toxicity and lethality (LD50) in mice and phytochemical constituents of the extract were also determined. Results The extract moderately inhibited the growth of the test organisms and significantly (P < 0.05) inhibited (57%) topical acute edema in the mouse ear. It significantly (P < 0.05) suppressed the development of acute edema of the rat paw in a non-dose-related manner and was not effective in inhibiting the global edematous response to formaldehyde arthritis. It also inhibited vascular permeability induced by acetic acid in mice and the haemolysis of ox RBCs induced by heat- and hypotonicity. The extract increased total leukocyte and neutrophil counts and caused a significant (P < 0.05) dose-related increase in the total number of macrophages at the 800 mg/kg dose. On phagocytic activity, the extract evoked a significant (P < 0.05) increase in the number of macrophages with ingested C. albicans at 800 mg/kg dose, and significantly (P < 0.05) inhibited DTHR in a dose-related manner. Phytochemical tests on the extract revealed an abundant presence of alkaloids and carbohydrates while saponins, glycosides, and terpenoids occurred in trace amounts. Acute toxicity test established an oral and intraperitoneal LD50 greater than 5,000 mg/kg. Conclusion The effectiveness of the root of A. montanus in the treatment of furuncles may largely derive from mobilization of leukocytes to the site of the infection and activation of phagocytic activity as well as suppression of exacerbated immune responses by its constituents. Antimicrobial and anti-inflammatory activities are likely contributory mechanisms. Phytochemical constituents such as alkaloids and carbohydrates may be responsible for these pharmacological activities.